Inflammatory Cascade in Aortic Wall: Latent Tuberculosis Complicating Takayasu Arteritis in a Young Bangladeshi Lady- The Silent Duo - Richmond Ronald Gomes (Indonesian Journal of Rheumatology, 2025)
Takayasu disease or pulseless disease is a rare chronic granulomatous panarteritis of unknown aetiology affecting large vessels, particularly the aorta and its main branches. It mainly affects females more than males with the ratio of 8:1 and in the second and third decade of life. Mechanism may be transmural fibrous thickening of the arterial walls. Takayasu arteritis is characterized by inflammation of the vessel wall, leading to occlusion of the vessel wall. It is represented with claudication, fever, and arthralgia. Clinical features are chest pain, vascular bruits, hypertension. There is indirect evidence signifying a potential link between tuberculosis (TB) and Takayasu’s arteritis (TAK); however, the exact mechanism and relationship between TAK and Mycobacterium tuberculosis (TB) remain elucidated. This case intends to highlight the association between latent TB and TAK, as early detection can avoid devastating consequences.